Pandemic, Therapy, and a Meditation on How: A Creative-Relational Inquiry. (June 2022) - Wyatt, Jonathan
"A creative-relational inquiry, " writes Dan Harris, "might be so small as to be imperceptible to the human eye . . . [b]ut it might also simultaneously be so big that whole universes exist within, between, and through it." In this brief article, I take up Harris' claim, writing into questions of scope and pace at this pandemic time, like how the small and the slow of an Edinburgh lockdown flutters into writing, poetic and therapeutic life, while around, within and beyond there is the multiplicity of the small, vast and fast of a virus. The text mutates with one small word, "how."